2006
DOI: 10.1007/s11746-006-5044-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting temperature‐dependence viscosity of vegetable oils from fatty acid composition

Abstract: The viscosities of 12 vegetable oils were experimentally determined as a function of temperature (5 to 95°C) by means of a temperature-controlled rheometer. Viscosities of the oil samples decreased exponentially with temperature. Of the three models [modified Williams-Landel-Ferry (WLF), power law and Arrhenius] that were used to describe the effects of temperature on viscosity, the modified WLF model gave the best fit. The amounts of monounsaturated FA or polyunsaturated fatty acids (PUFA) highly correlated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(157 citation statements)
references
References 20 publications
6
136
3
4
Order By: Relevance
“…26 The fatty acid composition of the aerial parts oil are presented in Table 2 that analyzed using a GC-FID for the first time from Iran. n-heptane extraction of T. parthenium herb aerial parts yielded 36% oil.…”
Section: Fatty Acids Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The fatty acid composition of the aerial parts oil are presented in Table 2 that analyzed using a GC-FID for the first time from Iran. n-heptane extraction of T. parthenium herb aerial parts yielded 36% oil.…”
Section: Fatty Acids Profilesmentioning
confidence: 99%
“…It seems that these valuable metabolites are affected by both genetic and environmental factors. 26 However, vegetable oils play important functional and sensory roles in food products, and they also provide energy and the essential fatty acids (monounsaturated or polyunsaturated), responsible for growth. …”
Section: Fatty Acids Profilesmentioning
confidence: 99%
“…Other rheological studies have confirmed this behavior on edible vegetable oils (Maskan, 2003;Fasina et al, 2006;Kim et al, 2010;Hassanien and Sharoba, 2014). This temperature dependence of viscosity of oils has been shown to be advantageous in application of vegetable oils in diesel engines to reduce wear and engine aging (Esteban et al, 2012).…”
Section: Effect Of Temperature On Viscositymentioning
confidence: 58%
“…2 shows the relationships between viscosity and temperature for waste cooking oil and diesel blends. Determination of viscosity as a rheological parameter is important considering the pumping process of fuel blends from one vessel to another such as storage tank to the furnace (Fasina et al, 2006). At room temperature (25°C), the viscosity of waste cooking oil (48 cP) was about 6 times that of diesel fuel (8 cP) in this study.…”
Section: Physiochemical Properties Of Fuel Blendsmentioning
confidence: 72%
“…mm per sec. are used as the working fluid in the hydraulic system of a dump truck with gear wheel pumps with an operating fluid temperature range from 0 to 80 °C [2,4].…”
Section: Methodsmentioning
confidence: 99%